Struck by stroke - experiences of living with stroke in a rural area in Uganda - Linda Timm; Julius Kamwesiga; Sulaiman Kigozi; Charlotte Ytterberg; Gunilla Eriksson; Susanne Guidetti (BMC, 2023)
Abstract Background The global burden of stroke is increasing and persons with low socioeconomic status are among those worst affected. In Uganda, stroke is estimated to be the sixth highest ranking cause of death. The Ugandan healthcare system is reported to be inequitable, where poorer populations often live in rural areas with long distances to health care. Stroke rehabilitation is often scarce, with less financial and human resources. The aim of this study was to explore and describe the consequences of stroke in daily activities in everyday life for people in a rural part of Masaka in Uganda. Methods Qualitative study design. Fourteen persons who had had stroke and were living in their home environment were interviewed about their experiences of having a stroke and managing their lives after the stroke incident. The interviews were analysed using thematic analysis. In addition, sociodemographic data and level of independence (Barthel Index and Stroke Impact Scale 3.0) was collected to describe participant characteristics. Results Most of the participants had major consequences of stroke and described that they were dependent on support for managing their daily activities. Five themes were identified in the analysis: (1) Accepting and adapting to new ways of managing everyday life, (2) Changing roles and hierarchical positions, (3) Depending on caregiver support, (4) Interrupted care due to economic constraints, (5) Stroke leading to losses and losses leading to stroke. Conclusions The consequences of stroke on the persons' daily lives clearly reached beyond the person with stroke, affecting the whole family and their proximate social networks. These consequences included increased burdens on caregivers and a worsened economic situation for all persons affected. Therefore, interventions for stroke management should preferably not only target the individual affected by stroke, but also support the caregivers in the caring and rehabilitation process. Home rehabilitation approaches with a focus on improving health literacy are suggested.